Impact of oral health education on oral health knowledge, attitude, and practices among 13-15 years' school-going children from Kanpur city, India: A quasi-experimental study - Devina Pradhan; Nidhi Pruthi; Lokesh Sharma; Jyothi Chavan; Pratik Verma (Wolters Kluwer Medknow Publications, 2020)
Background: Oral health is fundamental to general health and well-being. Schools may serve as the best platform for the promotion of oral health. Thus, it is essential to promote oral health in schoolchildren as they are the future of our nation. Aim: The aim of this study was to assess the impact of oral health education (OHE) on the knowledge, attitude, and practice of 13-15-year-old schoolchildren. Materials and Methods: A quasi-experimental study was conducted on a total of 876 schoolchildren aged 13-15 years of age. They were assessed for their oral health knowledge, attitude, and practice at the start of the study using a specially designed questionnaire. OHE was imparted to the children at baseline, 2 months, 4 months, and 6 months. All the children were later reassessed for their oral health knowledge, attitude, and practice using the same specially designed questionnaire after 6 months. Statistical analysis was done using Statistical Package for the Social Sciences (SPSS) version 21. Chi-square test was used for comparing the categorical data. Results: The schoolchildren in the study group showed higher levels of knowledge, attitude, and oral hygiene practices after OHE at the end of 6 months. Before and after the intervention, the scores were found to be statistically significant (P < 0.001). Conclusion: The OHE imparted proved to be effective in improving the oral health knowledge, attitude, and practices of schoolchildren.